Assessment of Physico-chemical Water Quality of Birecik Dam, Şanlıurfa, West East Region, Turkey - Kutlu, Banu; Sesli, Ahmet; Tepe, Rıdvan; Mutlu, Ekrem (Turkish Science and Technology Publishing (TURSTEP), 2015)
In year 2013, onsite seasonal measurements have been carried out in 4 different points of Birecik Reservoir, and water samples have been taken from surface and different depths. Physical and chemical parameters have been investigated in taken water samples. The result of analysis were obtained in the following range pH (6.98-9), temperature (9.9-26 °C), electrical conductivity (275-373 µs/cm), sodium ( 19.93-22.06 mg/L), potassium (1.-2.2 mg/L), chloride/11.68-21.4, hardness (179-210 mg/L), calcium (41.66-52.9 mg/L), magnesium ((17-18.35 mg/L), sulphate (27.92-43.48 mg/L), dissolved oxygen (7.92-8.83 mg/L), chemical oxygen (0.25-8.70 mg/L), nitrate (0.62-2.48 mg/L), nitrate (0.001-0.008), ammonium (0.01-0.07), phosphate (0.001-0.031 mg/L). The samples were compared with standard values recommended by world health (WHO). The study finalize that Birecik reservoir which was declared to be a threat to the water quality should be arrested at denitrification and nutrient control to halt the degradation of the water.
Keywords: Seasonal; Fiziko-Kimyasal Parametreler; S; Agriculture (General); Birecik Reservoir; Agriculture; Birecik Baraj Gölü; Physiochemical parameters; Mevsimsel; S1-972; Water quality; Birecik reservoir; Water Quality; Su Kalitesi; Physiochemical Parameters; 6. Clean water; 13. Climate action; 14. Life underwater